2017
DOI: 10.1039/c7ra05401g
|View full text |Cite|
|
Sign up to set email alerts
|

Millifluidic synthesis of cadmium sulfide nanoparticles and their application in bioimaging

Abstract: In this work, a miniature fluidic synthesis platform utilizing millimeter dimension channels yielding highly reproducible batch synthesis of luminescent cadmium sulfide (CdS) quantum dots and nanocrystals is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…Solid nanoparticles ranging from 5 to 150 nm in diameter have emerged as promising imaging and therapeutic agents. For example, CdS QDs can be used for optical imaging and gold nanorods for photoacoustic imaging, whereas iron oxide or Gd‐loaded nanoparticles can be applied to magnetic resonance imaging. MDs have been used for simple, robust, and high‐throughput generation of more advanced imaging materials such as protein‐lipid‐coated perfluorobutane microbubbles (about 3 µm) which were incorporated with various silica‐coated nanoparticles (CdSe/ZnS QDs, gold nanorods, iron oxide nanoparticles, and Gd‐loaded mesoporous silica nanoparticles).…”
Section: Biomedical Applications Of Microfluidic Fabricated Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Solid nanoparticles ranging from 5 to 150 nm in diameter have emerged as promising imaging and therapeutic agents. For example, CdS QDs can be used for optical imaging and gold nanorods for photoacoustic imaging, whereas iron oxide or Gd‐loaded nanoparticles can be applied to magnetic resonance imaging. MDs have been used for simple, robust, and high‐throughput generation of more advanced imaging materials such as protein‐lipid‐coated perfluorobutane microbubbles (about 3 µm) which were incorporated with various silica‐coated nanoparticles (CdSe/ZnS QDs, gold nanorods, iron oxide nanoparticles, and Gd‐loaded mesoporous silica nanoparticles).…”
Section: Biomedical Applications Of Microfluidic Fabricated Materialsmentioning
confidence: 99%
“…By far, CdS and CdSe are the most intensely studied in terms of using microfluidics for their fabrication, offering an effective and simple approach to access ultrasmall nanoparticles with low polydispersity compared to particles generated using conventional methods . Hong et al demonstrated control in the size and morphology of CdS nanocrystals (spheres, nanorods, and multipods, ranging in size from 2.6 to 6.7 nm in diameter) in a millifluidic chip, and used them in in vitro bioimaging using RAW264.7 mice macrophage cells ( Figure b). Tunable photoluminescence is possible by adjusting the molar ratio of the Cd and S precursors, giving rise to shifts in emission peaks under UV irradiation.…”
Section: Biomedical Applications Of Microfluidic Fabricated Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevada área superficial e baixa citotoxicidade são características que tornam interessante o uso de materiais nanoparticulados. Na literatura, vários trabalhos relatam a síntese de nanopartículas metálicas, tais como: Au [8][9][10], Ag [11][12][13], Co [14,15] e Cd [16,17].…”
Section: Introductionunclassified